FKKSAs outbound exchange students to Turkey India and Indonesia - Norhidayah, Mohamad (2018)
Faculty of Chemical Engineering & Natural Resources (FKKSA) has sent 13 students abroad to join the student exchange program at UMP’s partner institutions in Turkey, India and Indonesia. “This program is aimed to gain valuable experience as student life and campus activities in overseas universities as well to learn about their different culture and language” said Associate Professor Dr Fatmawati Adam, FKKSA Exchange Program Coordinator. Currently, the students are studying for one undergraduate semester from January to June 2018.